Digital Business Transformation: Innovation and Competitiveness Strategies in the Economy 4.0 Era - Hamiduddin, Ahmad Yahya (CV. Civiliza Publishing, 2025)
This study discusses digital business transformation as a strategy for innovation and increased competitiveness in the era of Economy 4.0. The background of this study stems from fundamental changes in the way companies operate, interact with consumers, and utilize digital technology as the main support for business activities. The objectives of this research are to analyze the digital transformation strategies pursued by business actors, identify the challenges faced, and formulate implications for competitiveness at the national and global levels. The research method used is a qualitative approach with a descriptive-analytical method. Data was collected through literature studies, in-depth interviews with business actors and experts, and non-participant observation of digital business practices in the e-commerce, fintech, and MSME sectors. Data analysis was carried out through the stages of reduction, presentation, and conclusion drawing using source triangulation techniques to ensure the validity of the findings. The results of the study show that digital transformation provides great opportunities to expand markets, improve efficiency, and create new innovation-based business models. However, the main challenges that arise include the internet access gap, low digital literacy, limited human resources, and data security threats. These findings confirm that the success of digital transformation depends not only on technology but also on the readiness of an ecosystem involving collaboration between the government, the private sector, academia, and the community. The implications of this research emphasize that digital business transformation is key to competitiveness in the global era, but it must be accompanied by inclusive strategies, supportive policies, and sustainable investment in human resource development. Thus, digital transformation can be a driving force for sustainable and equitable national economic growth.